The Effects of Spatial Experience on the Designs of First Year Architecture Students - Yazici, Yasemin Erkan; Erdogan, Meral (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2011)
Designers often call on their past experiences in order to solve new design problems. Information recalled from the memories of past spatial experiences play an important role in the establishment of the framework to be used when solving the current design problem. However, recalled information may be related to methods or certain aspects of the previous solutions of similar design problems which may not always be appropriate to the problem at hand. Therefore, such remembered spatial experiences may have adverse effects on the design process, for instance in the form of design fixation, a difficulty which may be more pronounced for inexperienced designers. This paper reports the findings of an experimental study which was devised to expose the possible adverse effects of previous spatial experiences on the designs of first year architecture students.
Keywords: Spatial memory; spatial experience; design fixation; Architecture